Rate of Neurologic Injury Following Lateralizing Calcaneal Osteotomy Performed Through a Medial Approach. (December 2017) - Jaffe, David; Vier, David; Kane, Justin; Kozanek, Michal; Royer, Christian
Background: Calcaneal osteotomies are commonly used to correct varus hindfoot alignment in patients with symptomatic cavovarus deformity. Translational, closing wedge, and Malerba-type osteotomies have been implicated in the development of tarsal tunnel syndrome and neurologic injury to branches of the tibial nerve. The authors hypothesized that there would be minimal clinically important injury to the tibial nerve by performing a translational calcaneal osteotomy from a medial approach. Methods: All patients undergoing a cavovarus reconstruction by a single surgeon were identified. Patients were included if they underwent a lateralizing calcaneal osteotomy via medial approach. Demographics, operative reports, and clinic notes were reviewed to identify concomitant procedures performed, incidence of postoperative tarsal tunnel syndrome, complications, and preoperative and postoperative nerve examinations. Postoperative radiographs were reviewed for location of the osteotomy relative to the posterior tubercle. Results: Twenty-four patients underwent lateralizing calcaneal osteotomy via a medial approach. Of the osteotomies, 83.3% (20/24) were in the middle third of the calcaneus, with a mean of 11.6-mm translation. No patients developed postoperative tarsal tunnel syndrome or tibial nerve palsy. Conclusion: Lateralizing calcaneal osteotomy performed via a medial approach had a clinically negligible incidence of neurologic injury. Adequate translation was achieved to obtain correction of varus hindfoot deformity. The authors believe that there is less direct and less percussive injury to branches of the tibial nerve when performing the osteotomy from medial to lateral. This technique may represent an operative strategy to minimize risk to the tibial nerve and reduce neurologic deficit following cavovarus reconstruction. Level of Evidence: Level IV, case series.